Fine particulate matter-sudden death association modified by ventricular hypertrophy and inflammation: a case-crossover study - Rappazzo, Kristen M.; Egerstrom, Nicole M.; Wu, Jianyong; Capone, Alia B.; Joodi, Golsa; Keen, Susan; Cascio, Wayne E.; Simpson, Ross J. (Frontiers in Public Health, 2024)
Background: Sudden death accounts for approximately 10% of deaths among working age adults and is associated with poor air quality. Objectives: To identify high risk groups and potential modifiers and mediators of risk, we explored previously established associations of fine particulate matter (PM2.5) and sudden death stratified by potential risk factors. Methods: Sudden death victims in Wake County, NC from 3/1/2013 -2/28/2015 were identified by screening Emergency Medical Systems reports and adjudicated (n=399). Daily PM2.5 concentrations for Wake County from the Air Quality Data Mart were linked to event and control periods. Potential modifiers included greenspace metrics, clinical conditions, left ventricular hypertrophy (LVH), and neutrophil to lymphocyte ratio (NLR). Using a case-crossover design, conditional logistic regression estimated OR (95%CI) for sudden death for a 5µg/m 3 increase in PM2.5 with a 1-day lag, adjusted for temperature and humidity, across risk factor strata. Results: Individuals having LVH or a NLR above 2.5 had PM2.5 associations of larger magnitude than those without (with LVH OR: 1.90 (1.04, 3.50); NLR>2.5: 1.25 (0.89, 1.76)). PM2.5 was generally less impactful for individuals living in areas with higher levels of greenspace. Conclusions: Left ventricular hypertrophy and inflammation may be the final step in the causal pathway whereby poor air quality and traditional risk factors trigger arrhythmia or myocardial ischemia and sudden death. The combination of statistical evidence with clinical knowledge can inform medical providers of underlying risks for their patients generally, while our findings here may help guide interventions to mitigate the incidence of sudden death.